Climate change impacts on global agriculture - Alvaro Calzadilla; Katrin Rehdanz; Richard Betts; Pete Falloon; Andy Wiltshire; Richard S. J. Tol (Universität Hamburg, Forschungsstelle Nachhaltige Umweltentwicklung, 2010)
Based on predicted changes in the magnitude and distribution of global precipitation, temperature and river flow under the IPCC SRES A1B and A2 scenarios, this study assesses the potential impacts of climate change and CO2 fertilization on global agriculture. The analysis uses the new version of the GTAP-W model, which distinguishes between rainfed and irrigated agriculture and implements water as an explicit factor of production for irrigated agriculture. Future climate change is likely to modify regional water endowments and soil moisture. As a consequence, the distribution of harvested land would change, modifying production and international trade patterns. The results suggest that a partial analysis of the main factors through which climate change will affect agricultural productivity lead to different outcomes. Our results show that global food production, welfare and GDP fall in the two time periods and SRES scenarios. Higher food prices are expected. Independently of the SRES scenario, expected losses in welfare are nmarked in the long term. They are larger under the SRES A2 scenario for the 2020s and under the SRES A1B scenario for the 2050s. The results show that countries are not only influenced by regional climate change, but also by climate-induced changes in competitiveness.
Keywords: D58; Q54; Q17; Q25; 330; Computable General Equilibrium; Climate Change; Agriculture; Water Resources; River Flow